Influence of connective tissue growth factor antisense oligonucleotide on angiotensin II-induced epithelial mesenchymal transition in HK2 cells - Chen Long; Liu Bi-cheng; Zhang Xiao-liang; Zhang Jian-dong; Liu Hong; Li Min-xia (Acta Pharmacologica Sinica, 2016)
Aim: The present study was designed to further investigate the effect of connective tissue growth factor antisense oligonucleotide (CTGF-AS) on angiotensin II (Ang II)-induced tubular cell epithelial mesenchymal transition (EMT) in vitro. Methods: The human proximal tubular cell line (HK2) was grown in Dulbecco's modified Eagle's medium containing 10% heat inactivated fetal calf serum. After being rested in serum-free medium for 24 h, the influence of CTGF-AS (20 μg/mL) on Ang II-induced (1×10-7 mol/L) CTGF mRNA and the protein expression were examined by using reverse transcription-polymerase chain reaction and indirect-immunofluorescence. The effect of CTGF-AS on Ang II-induced cellular ultra-structure was observed using a transmissive electronic microscope. The expression of α-smooth action (α-SMA) was assayed by immunocytochemistry. In all experiments, the control group was treated with scrambled oligonucleotide. Results: It was shown that Ang II significantly induced the increasing expression of CTGF mRNA and protein (P